Game as a Phenomenon in Kyrgyz Family Traditions - Saadanbekova, Cholpon (Տիգրան Մեծ)
The relevance of the philosophical understanding of the concept of “game” is caused by the great inter-est in this phenomenon from the humanities and mathematical sciences (game theory). The subject of research is the socio-philosophical aspects of the game in the Kyrgyz family traditions. The purpose of the study is to conduct a historical and philosophical analysis of the game component within the framework of the specifics of the Kyrgyz ethnos. In the course of our research, we identified such properties of a game as non-utilitarianism, irrationality, the presence of rules, aesthetics, and the predominance of the child over the adult. We conclude that the nomadic and rhizomatic structure of Kyrgyz society played a decisive role in the sustainability of the transmission of family traditions through the game component. The author analyzed the game component of social matter during the main historical periods of the Kyrgyz ethnos and stages of psychosocial development. The following methods were used conceptual analysis, synchronic and diachronic method, comparative-historical approach, network methodology with elements of the poststructuralist topological approach.
Keywords: Philosophy of law; Family relations